Allele frequencies of STRs F13A01, FES/FPS and vWA in random temiar population of Gua Musang, Malaysia - Shahril, Alliai (Universiti Sains Malaysia, 2008)
Allelic distribution for three validated STRs (Fl3A01, FESFPS, vWA) in a population sample of 100 random individuals of Temiar population in Gua Musang, Malaysia was compiled for use in forensic case work. DNA was extracted from buccal cells using organic method. Genotype of 1 00 random individuals was ascertained by using multiplex primer kit. Allelic frequencies and statistical parameters such as heterozygosity, power of exclusion and power of discrimination were calculated. No significant deviation from Hardy Weinberg equilibrium was observed. The allele distribution for each of the STR marker studied was compared with other published data bases. Distribution of alleles for the three validated STRs in Temiar population is unique.